Breast Cancer‐Derived Exosomes Reflect the Cell‐of‐Origin Phenotype - Shu Wen; Luize Goncalves Lima; Richard J. Lobb; Emma L. Norris; Marcus L. Hastie; Sophie Krumeich; Andreas Möller (2019)
Abstract A manner in which cells can communicate with each other is via secreted nanoparticles termed exosomes. These vesicles contain lipids, nucleic acids, and proteins, and are said to reflect the cell‐of‐origin. However, for the exosomal protein content, there is limited evidence in the literature to verify this statement. Here, proteomic assessment combined with pathway‐enrichment analysis is used to demonstrate that the protein cargo of exosomes reflects the epithelial/mesenchymal phenotype of secreting breast cancer cells. Given that epithelial‐mesenchymal plasticity is known to implicate various stages of cancer progression, the results suggest that breast cancer subtypes with distinct epithelial and mesenchymal phenotypes may be distinguished by directly assessing the protein content of exosomes. Additionally, the work is a substantial step toward verifying the statement that cell‐derived exosomes reflect the phenotype of the cells‐of‐origin.